Germinal center centroblasts transition to a centrocyte phenotype according to a timed program and depend on the dark zone for effective selection. - Bannard, O; Horton, R; Allen, C; An, J; Nagasawa, T; Cyster, J (2013)
Germinal center (GC) B cells cycle between the dark zone (DZ) and light zone (LZ) during antibody affinity maturation. Whether this movement is necessary for GC function has not been tested. Here we show that CXCR4-deficient GC B cells, which are restricted to the LZ, are gradually outcompeted by WT cells indicating an essential role for DZ access. Remarkably, the transition between DZ centroblast and LZ centrocyte phenotypes occurred independently of positioning. However, CXCR4-deficient cells carried fewer mutations and were overrepresented in the CD73(+) memory compartment. These findings are consistent with a model where GC B cells change from DZ to LZ phenotype according to a timed cellular program but suggest that spatial separation of DZ cells facilitates more effective rounds of mutation and selection. Finally, we identify a network of DZ CXCL12-expressing reticular cells that likely support DZ functions.